Implications for forensic death investigations from first Swiss post-mortem CT in a case of non-hospital treatment with COVID-19. (June 2020) - Schweitzer, Wolf; Ruder, Thomas; Baumeister, Rilana; Bolliger, Stephan; Thali, Michael; Meixner, Eva; Ampanozi, Garyfalia
Highlights: 3D Visualisation of lung pathology allows to better estimate the distribution of aerated, poorly aerated and non-aerated lung regions Forensic COVID-19 autopsy apparently showing a different (higher) degree of pathology than hospital autopsy reports compared to SARS-COV-2, but on par with SARS. Abstract: Case details: A case of a 50-year old HIV-positive man is presented, with focus on visualization of post-mortem computed tomography (PMCT) of the lungs, in comparison to a forensic control case. He had been found dead at home, a day after his nasopharyngeal swab had returned positive for SARS-COV-2, three days after the sample had been taken as an outpatient, over five weeks after first exhibiting possible symptoms. 3D-visualization was performed by visually discriminating correlates for aerated, poorly aerated and non-aerated lung regions. The visual side-by-side comparison with a control case shows the deterioration beyond any "normal" post-mortem finding, however. The PMCT findings in the lungs resemble those of patients with acute respiratory distress syndrome (ARDS), while histologically identified inflammation also shows, in part binuclear, lymphocytes. In addition, acute liver dystrophy and acute tubular necrosis in the kidneys were found. Except coronary artery atherosclerosis, there appeared to be no remarkable pathology of the heart. Comment: With the pandemic impact of SARS-COV-2, a range of issues unfolds, also for medicolegal investigations into deaths, as we report the first Swiss case with post-mortem CT where death had occurred due to a SARS-COV-2 infection, with features of a severe acute respiratory distress syndrome, as an outpatient. As this pandemic from the view of risk assessment does constitute a black swan, underestimated fat tails as technical reason should be addressed by also analyzing apparent extreme single observations. This case of an outpatient (without hospital or intensive-care treatment) shows a pulmonary progression beyond the typical findings of COVID-19, to a non-specific picture of ARDS, where histologically, in part binuclear lymphocytes were remarked. What appeared to be an initially slow progression with final rapid escalation raises the question whether nasopharyngeal swabs alone or added pulmonary CT might be better for screening high-risk patients. The reported symptoms and relatively late medical consultation in this case appeared to contrast with the extensive pathology, raising the question whether any search for super-spreaders should not just focus on asymptomatic but under-reported symptomatic patients, and whether their prolonged circulation in everyday life would justify measures such as for example more extensive face mask policies. As post-mortem testing for SARS-COV-2 may not be available for every case, PMCT may provide sensitive testing for lung changes related to COVID-19. In order to allow for more precise medicolegal investigations in the context of COVID-19, however, any more specific extra tests may have to be financed by stakeholders in epidemiology, infectious disease or policy.